ТҮН ҲӘМ ҚАРАҢҒЫЛЫҚ ОБРАЗЛАРЫНЫҢ РОМАНЛАРДА СҮЎРЕТЛЕНИЎИ - Сейтниязов, Т. (FAN va JAMIYAT, 2025)
The article discusses the depiction of natural scenes in Karakalpak prose. In Karakalpak novels, the relationship of time to events, as well as the relationship of characters to time, has been analyzed. The day and night events in the literary work, their connection to the action and the development of events, were studied.